2022-RA-181-ESGO Updated systematic review about results of fertility sparing surgery of cervical cancer. (20th October 2022) - Gouy, Sebastien; Scherier, Stephanie; Maulard, Amandine; Zaccarini, Francois; Zarokian, Julie; Sanson, Claire; Espenel, Sophie; Leary, Alexandra; Pautier, Patricia; Genestie, Catherine; Chargari, Cyrus; Grynberg, Michael; et al.
Abstract : Introduction/Background: Six different techniques can be proposed to preserve the uterine corpus in early stage cervical cancer. Oncologic results (particularly recurrence rates) are the first aim of this review in order to evaluate the best strategy according both to the tumor size (< or > 20 mm) and the lympho-vascular space involvement status. When the results comparing different strategies are weighed, fertility results are analysed. Methodology: Data were identified from searches of MEDLINE, Current Contents, PubMed and from references in relevant articles from 1st of January 1987 to 15th of September 2021. We carry out an updated systematic review involving 5, 862 patients initially selected for fertility-sparing surgery in 275 series. Results: In patients having a tumor size < 20 mm (stage IB1 disease), recurrence rates (RR) in patients undergoing simple conisation/trachelectomy, radical trachelectomy/RT by laparoscopico-vaginal approach, laparotomic or laparoscopic approaches are respectively: 4.1%, 4.7%, 2.4% and 5.2%. In patients having a tumor size between 20 mm and 40 mm (stage IB2 disease), recurrences rates in patients undergoing neo-adjuvant chemotherapy or RT by laparotomy are respectively 13.2% and 4.8% (p=.0035). In patients having tumor size < 40 mm, RR observed in patients undergoing an open or a mini-invasive approach are respectively: 3.3% and 5.5% (NS). The lowest pregnancy rate is observed in patients undergoing RT by laparotomy (36%). Conclusion: The choice between these treatments should be based on the experience of the teams, on the discussion with the patient/couple but, above all, on objective oncological data. In patients having a stage IB1 disease, oncological results are quite similar according to the procedure used. In patients having a stage IB2 disease, RT by open approach should be preferred. Anyway the lowest pregnancy rate is observed in patients undergoing RT by laparotomy